J-aggregate formation behavior of a cationic cyanine dye on inorganic layered material. Issue 22 (27th May 2015) - Sato, Narumi; Fujimura, Takuya; Shimada, Tetsuya; Tani, Tadaaki; Takagi, Shinsuke
Graphical abstract: Abstract: Adsorption, aggregation, and photochemical behavior of a cationic cyanine dye (5, 5′, 6, 6′-tetrachloro-1, 1′, 3, 3′-tetraethylbenzimidazolylcarbo-cyanine chloride (JC-1)) on an inorganic layered material were examined. JC-1 formed J-aggregates on the clay surface even at a low loading level. The structure of the J-aggregate was determined through analysis using the extended dipole model proposed by Kuhn et al. Aggregation number and slip angle of the J-aggregate on the clay surface were calculated as more than 8 molecules and 20–22°, respectively. The J-aggregate on the clay sheet exhibited high fluorescence quantum yield (0.4), thus, this complex will be promising to construct photochemical reaction systems such as artificial light harvesting systems.